Advances of Naturally Derived and Synthetic Hydrogels for Intervertebral Disk Regeneration - Tang, Guoke; Zhou, Bingyan; Li, Feng; Wang, Weiheng; Liu, Yi; Wang, Xing; Liu, Chao; Ye, Xiaojian (Frontiers in Bioengineering and Biotechnology, 2020)
Low back pain, one of an extremely common disease syndrome, causes the pain and disability in patients, which is urgently needed to improve the life quality of the patients. Intervertebral disc (IVD) degeneration is reported to be related to most cervical and lumbar spine diseases, of which chronic low back pain has become the primary cause for the loss of quality-adjusted life-year. Biomaterials science and tissue engineering have made significant progress in the replacement, repair and regeneration of intervertebral disc tissue. Hydrogels are recognized as effective methods to promote IVD regeneration in recent years. Aspects such as ease of use, mechanical properties, regeneration capabilities and their suitability are suitable for IVD regeneration. The current review provides an overview of naturally-derived and synthetic hydrogels that are related to their clinical applications for intervertebral disc regeneration. Although each type has its own unique advantages, it rarely becomes a standard in clinical practice. At present, the research to find a better method of IVD regeneration is still continuing. This review aims to provide a starting point and inspiration for future research work on developing a generation of biomaterials and biotechnology.